All‐cause and cardiovascular disease mortality in underweight patients with diabetic nephropathy: BioBank Japan cohort. Issue 8 (18th January 2021) - Yokomichi, Hiroshi; Mochizuki, Mie; Hirata, Makoto; Nagai, Akiko; Kojima, Reiji; Horiuchi, Sayaka; Ooka, Tadao; Akiyama, Yuka; Shinohara, Ryoji; Miyake, Kunio; ,; Yamagata, Zentaro
Abstract: We aimed to determine mortality risk in underweight patients with diabetic nephropathy for microalbuminuria or macroalbuminuria. We analyzed mortality and death‐cause data from BioBank Japan, with baseline years 2003–2007. We analyzed mortality rates from all causes and ischemic heart disease, according to body mass index (<18.5, 18.5–21.9, 22–24.9 and ≥25 kg/m 2 ). The mean (standard deviation) of patient age, body mass index, and glycated hemoglobin at enrollment was 61.6 years (11.7 years), 25.0 kg/m 2 (4.4 kg/m 2 ) and 7.7% (1.5%), respectively. Hazard ratios of all‐cause and ischemic heart disease mortality were highest (1.79 [ P  = 0.0001] and 2.95 [ P  = 0.027], respectively) in patients with body mass index <18.5 kg/m 2, as compared with body mass index 22–24.9 kg/m 2 . All‐cause mortality risk for body mass index <18.5 kg/m 2 was similar to that for current smokers (hazard ratio 1.70, P  < 0.0001). Underweight could be a predictor of mortality risk in patients with diabetic nephropathy for microalbuminuria or macroalbuminuria. Abstract : Comparison of mortality by body mass index categories among Japanese patients with diabetic nephropathy for microalbuminuria and macroalbuminuria. Body mass index for <18.5 kg/m 2 had the highest, and body mass index for 18.5–21.9 kg/m 2 had the second highest mortality.